Expression of Bhakti - Mumbai Archive Project Team (Jio Institute, 2024)
Krishna Janmashtami is not only a celebration of Sri Krishna's birth but also an expression of bhakti (devotional love) by his devotees, which is an integral part of Krishna’s leela (divine play).